Prognostic Factors of Survival in Veno-Arterial ECMO Patients: A Multivariable Logistic Regression Analysis - Andrew Jones; George Olverson IV; Wayne Wong; Rohun Bhagat; Clauden Louis (University Library System, University of Pittsburgh, 2023)
Background: Several models exist to predict mortality in patients on Veno-arterial (VA) extracorporeal membrane oxygenation (ECMO).  Whether expanded demographic data points have prognostic implications is less understood. This study assessed the prognostic value of demographics in patients on VA-ECMO. Methods: This retrospective cohort study investigated 410 patients who received VA-ECMO.  Survival to hospital discharge, survival to intensive care unit discharge and survival to ECMO explantation were examined. A multivariable logistic regression was performed incorporating 11 demographic variables. Results: 44% (181/410) of patients survived to ECMO explant, 37% (152/410) of patients survived to ICU discharge, and 36% (146/410) of patients survived to hospital discharge. There was an increase in odds of survival to hospital discharge in patients who were less than 55 years old (Odds Ratio (OR) = 3.91 [95% Confidence Interval (CI) 2.35-6.49]). There was a decrease in odds of survival to hospital discharge in patients who had a prior cardiac arrest (OR = 0.35 [95% CI 0.20-0.63]). Patients who survived to hospital discharge less frequently had a history of smoking (51% vs 65%, respectively; p=0.008), and were younger compared to those who did not survive (51.4+/- 14.03 vs 57.3+/- 16.54). Conclusion: Age less than 55 years old was a prognostic indicator of survival to hospital discharge following VA-ECMO, while history of smoking, history of dialysis, and history of cardiac arrest were associated with mortality. Sex, BMI, atrial fibrillation, hypertension, DM, and COPD were not significant indicators. These data may help guide optimal patient selection for VA-ECMO support.